Spatial and technological organization of Novosibirsk university campuses - E. A. Volkova; J. E. Nizhegorodtseva; A. A. Moroz (Vestnik MGSU, 2023)
Introduction. The article is focused on the modern criteria of the university campus’s architectural and spatial organization. The authors identify some campuses typologies. Using this information, they analyze Novosibirsk higher educational institutions and their placement features in the city’s structure. Finally proposed classification, based on functional saturation and technological features, reflects the types of existing campuses in Novosibirsk. The result of this analysis in a conclusion whether the territorial organization of Novosibirsk universities meets the modern requirements of the campus.Materials and methods. Based on the study of electronic, written and literary sources, various variants of the typology of university campuses are analyzed. Generalization and comparison of data on the constituent universities was carried out on the basis of comparative analysis. The conceptual modeling reflects the architectural and spatial features of the placement of university campuses, as well as their functional saturation.Results. Territorial typological features of the location of campuses in the structure of cities are revealed. On the example of university campuses in the city of Novosibirsk, their spatial organization is indicated. In order to determine the features of the technological organization of Novosibirsk universities, a comparative analysis of the functional components of the university was carried out and a conceptual campus model relevant for Novosibirsk universities was presented.Conclusions. Based on this analysis, it is concluded whether the territorial organization of Novosibirsk universities meets the modern requirements of the campus.